The Three Stages Law of Auguste Comte and Its Contribution to the Study of Sociology - Rahmatullah; Shermina Oruh; Andi Agustang (Universitas Muhammadiyah Palu, 2024)
This article aims to explain Auguste Comte's three-stage law of epistemology in the theory of social change, namely the theological, metaphysical, and positive stages, and to explore its relevance to the study of sociology. The article employs qualitative research with a literature review approach. This method is utilized to gather information and data through various materials available in the library, such as documents, books, magazines, and so on. Comte attempts to elucidate that social change occurs in three stages: the Theological Stage (fictional), the Metaphysical Stage (abstract), and the Positive Stage (scientific). These three stages are considered universal laws that generalize the evolution of society throughout its history. Comte proposes that the positive stage represents the pinnacle of human thought evolution, and sociology, as a science, should adopt a positivistic approach focused on empirical analysis and objective observation to understand the structure and function of society. The positive stage is viewed as the culmination and highest point in the development of human intelligence, where humans seek to understand all relationships within the order of nature through scientific approaches and empirical data. This pursuit aims to shape human intelligence for more advanced and progressive living.